Management of diabetes mellitus and patients' attitude towards the disease: Data from a nationwide study in Greece. Issue 2 (March 2019) - Tentolouris, Anastasios; Eleftheriadou, Ioanna; Tzeravini, Evangelia; Athanasakis, Kostas; Anastasiou, Ioanna A.; Kyriopoulos, John; Tentolouris, Nikolaos
Abstract: Aim: To examine management of diabetes mellitus (DM) and patients' attitude towards DM in a random sample of the adult Greek population. Methods: s : We selected a random sample of adults with self-reported DM (n = 1002) from a population-based nationwide study using the effective random sampling technique. Collection of data was performed through phone interviews. Results: Prevalence of type 1 DM was 3.5% and of type 2 DM 96.5%. Prevalence of type 1 DM declined while of type 2 DM increased with age. No gender or residency differences were found between type 1 and type 2 DM. A total of 72.0% of subjects with type 2 DM were treated with oral antidiabetic drugs (OAD), 11.5% were treated with insulin and 7.1% were treated with both OAD and insulin. Internists specialized in DM were mainly doctors who started insulin treatment. Almost half of insulin naive subjects were skeptical towards insulin initiation and their main concern was the needle punch. Conclusions: In a random nationwide sample of the adult population in Greece the majority of subjects with self-reported DM had type 2 DM. Most patients with type 2 were treated with OAD. Almost half of insulin naive subjects were skeptical towards insulin initiation.